KETEPATAN WAKTU PELAPORAN KEUANGAN (Fokus Ekonomi, 2008)
Financial reports give important information about the performance of corporates. There have been extensive literature studies which examine the determinant of timeliness financial reporting to public. This paper explore factors which influence timeliness financial reporting to public. The factors are debt to equity ratio, company size, profitability, insider ownership, and outsider ownership. Keywords: Financial Reporting, Timeliness, Profitability, Debt To Equity Ratio, Company Size, Insider Ownership and Outsider Ownership.